Breast Lesions Diagnosed as Ductal Carcinoma In Situ by Ultrasound-Guided Core Needle Biopsy: Risk Predictors for Concomitant Invasive Carcinoma and Axillary Lymph Node Metastasis - Liu, Yanbiao; Wang, Xu; Zheng, Ang; Yu, Xinmiao; Jin, Zining; Jin, Feng (Frontiers in Oncology, 2021)
Background The major concern over preoperatively diagnosed ductal carcinoma in situ (DCIS) of breast via ultrasound-guided core needle biopsy (US-CNB) is the risk of missing concomitant invasive carcinoma. It is crucial to identify risk predictors for such a phenomenon and evaluate its impact on axillary conditions to help surgeons determine which patients should receive appropriate axillary lymph node management. Methods Medical records of 260 patients preoperatively diagnosed with DCIS via 14-gauge CNB were retrospectively analyzed. All of them underwent subsequent surgery at our institution and were successively divided into invasive and non-invasive groups, and metastatic and non-metastatic groups according to pathology of resected specimens and metastasis of axillary lymph nodes (ALNs). Predictive value of preoperative physical examinations, imaging findings, histopathological findings, and hematological indexes for pathological underestimation and metastasis of ALN was assessed by logistic regression analysis. Results The concomitant invasive carcinoma was overlooked in 75 out of 260 patients (29.3%). Multivariate analysis revealed that presence of microinvasion, presence of abnormal lymph node on ultrasound, and absent linear or segmental distributed calcification on mammography were independent risk predictors for invasive carcinoma. Fourteen patients had lymph node metastasis, and five of them were in the non-invasive group. The presence of abnormal lymph node on ultrasound and increased ratio of platelet distribution width to platelet crit (PDW/PCT) (>52.85) were identified as independent risk predictors for ALN metastasis. Conclusion For patients diagnosed with DCIS preoperatively, appropriate ALN management is necessary if they have risk predictors for concomitant invasive carcinoma and ALN metastasis.